Neuropsychiatric Complications after Stroke - Nemani, Katlyn; Gurin, Lindsey (Seminars in Neurology, 2021)
Neuropsychiatric disturbances represent a common and uniquely challenging consequence of stroke. These disorders arise at the intersection of lesion-related brain dysfunction and psychological distress related to the event and its aftermath, making it difficult to identify what symptom is a direct physiological consequence of the stroke. Depression, anxiety, fatigue, apathy, emotionalism, and anger are the most common of these syndromes, and posttraumatic stress disorder related to the stroke event has become increasingly recognized as a relevant entity. Mania, obsessive–compulsive disorder, and psychosis are less commonly encountered but potentially highly debilitating conditions that may be underrecognized. Early identification and treatment may mitigate functional impairment and improve quality of life. Evidence-based guidelines from the general population are often relied upon to guide treatment. Further research is needed to understand and tailor treatment of these disorders in the poststroke population.
Keywords: stroke; neuropsychiatry; poststroke depression; anxiety; posttraumatic stress disorder; fatigue; apathy; emotionalism; anger; psychosis